64Cu tumor labeling with hexadentate picolinic acid-based bispidine immunoconjugates - Kubeil, Manja; Neuber, Christin; Starke, Miriam; Arndt, Claudia; Rodrigues Loureiro, Liliana; Hoffmann, Lydia; Feldmann, Anja; Bachmann, Michael; Pietzsch, Jens; Comba, Peter; Stephan, Holger (Chemistry - a European journal, 2024)
Discussed are two picolinate appended bispidine ligands (3,7-diazabicyclo[3.3.1]nonane derivatives) in comparison with an earlier described bis-pyridine derivative, which are all known to strongly bind CuII. The radiopharmacological characterization of the two isomeric bispidine complexes includes quantitative labeling with 64CuII at ambient conditions with high radiochemical purities and yields (molar activities >200 MBq/nmol). Challenge experiments in presence of EDTA, cyclam, human serum and SOD demonstrate high stability and inertness of the 64Cu-bispidine complexes. Biodistribution studies performed in Wistar rats indicate a rapid renal elimination for both 64Cu-labeled chelates. The bispidine ligand with the picolinate group in N7 position was selected for further biological experiments, and its backbone was therefore substituted with a benzyl-NCS group at C9. Two tumor target modules (TMs), targeting prostate stem cell antigen (PSCA), overexpressed in prostate cancer, and the fibroblast activation protein (FAP) in fibrosarcoma, were selected for thiourea coupling with the NCS-functionalized ligand and lysine residues of TMs. Small animal PET experiments on tumor-bearing mice showed specific accumulation of the 64Cu-labeled TMs in PSCA- and FAP-overexpressing tumors (standardized uptake value (SUV) for PC3: 2.7±0.6 and HT1080: 7.2±1.25) with almost no uptake in wild type tumors.
Im Titel ist 64 hochgestellt
Online verfügbar: 20. März 2024
Gesehen am 22.10.2024